IMPLEMENTASI MODEL PEMBELAJARAN TEAM GAMES TOURNAMENT (TGT) UNTUK MENINGKATKAN MOTIVASI INTRINSTIK PADA SISWA DALAM PEMBELAJARAN IPAS KELAS 4 SDN 083 BABAKAN SURABAYA - Ghina Khalishah Salsabila (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2025)
This research aims to explore the implementation of the Team Games Tournament (TGT) cooperative learning model in enhancing intrinsic motivation among fourth-grade students at SDN 083 Babakan Surabaya in IPAS subject (Natural and Social Sciences), specifically on the topic of changes in states of matter. Using a descriptive qualitative method, the study involved 28 students and collected data through direct classroom observations, student worksheets (LKPD), evaluation forms, and open-ended questionnaires. The findings show that 86% of the students demonstrated high intrinsic motivation, collaborative behavior, and active participation during learning sessions using the Team Games Turnament (TGT) model. Students found the group activities fun and engaging, indicating a boost in curiosity, perseverance, and self-confidence. While a small portion (14%) of the students remained passive, the overall learning atmosphere was participatory and enjoyable. Most groups completed the LKPD accurately, suggesting improved understanding of the subject matter. The results highlight Team Games Turnament (TGT) role in creating a learning environment that fosters academic interest, emotional involvement, and positive student interaction. Consequently, this model proves to be effective in increasing students’ intrinsic motivation and conceptual grasp in elementary science education.